Polymerizability of aliphatic cyclic esters - Duda, A.; Kowalski, A. (Polimery, 2022)
The fundamental factors influencing polymerizability of aliphatic cyclic esters (lactones, lactides and carbonates - see Scheme A) were discussed on the basis of literature review. Thermodynamic factors (a) related mostly to the monomer ring strain and the numbers of degrees of freedom of the polymer repeating units as well as kinetic factors (b) resulting from the polymerization mechanism availability securing the sufficient polymerization rate were distinguished. An attention was paid to the fact that thermodynamically determined inability of cyclic ester to polymerize was not tantamount to its inability to ring-opening reaction. The syntheses of macromolecular copolymers containing up to 50-mole % of repeated units coming from non-homopolymerizable monomer are possible. The analysis of kinetic factors allowed concluding that there was no uniform correlation between monomer reactivity and ring size. Moreover, dependently on the polymerization mechanism, the reversed reactivity order could occur. The methods of polymer yield increasing, in connection with disadvantageous occurring (in some cases) of substantial equilibrium concentrations of monomer and cyclic oligomers were also discussed.